Implementing Blended Learning in Bangladeshi Universities: Challenges and Opportunities from Student Perspectives - Chowdhury, Md Khaled; Behak, Fariza Binti Puteh (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
Blended education has been used worldwide for the last two decades as an alternative to full online education but not in Bangladesh. There was never any significant attempt to investigate people’s perception or experience of blended learning in Bangladesh. Therefore, this study tries to investigate the people’s experiences with this new method, a three-month-long blended course in English Writing Skill was offered at a private university in Bangladesh, where eighteen students registered for the course. After completing the course, an open-ended interview protocol was used to collect primary data from 11 students. This qualitative research is based on an interview with 11 samples and other comments posted on Google classroom and Facebook. The interview contained 8 open-ended questions to elicit their experiences with the blended learning method, a new method for them on the one hand, and both face-to-face and online education. We also investigated the 4 essay scores of these 11 respondents to check whether their performance improved due to peer and teacher feedback on those essays in the blog created and used for posting student essays. The majority of respondents have a highly positive opinion about the blended method for its positive impacts such as peer interaction and peer support, teacher feedback, as is evident from their improved scores in the successive essays, and other advantages such as learning varieties, flexibility and self-paced learning and quality of education. However, they mention a number of challenges in its implementation. It seems that blended courses will effectively reduce session backlog and cost of higher education, increase student-student and student-teacher interaction and ensure flexibility and quality of higher education in comparison with face-to-face and online education. This study is important for Bangladeshi higher education institutions because it is expected to enlighten policymakers about the importance of blended education.